(untitled) (Innovate Conferences, 2025)
Currently, there is very little information on the epidemiology, clinical features, prevention and treatment of Post-Covid-19 Associated Gastrointestinal Diseases (Post-Covid-19 Associated Gastrointestinal Diseases) and none at all in Uzbekistan and, in particular, in the Fergana Valley. According to the scientific results obtained in clinical trials, there is every reason to believe that patients with digestive system diseases may be a risk group for severe disease and unfavorable prognosis when infected with the SARS-CoV-2 virus. [1]. Post-Covid-19 Associated Gastrointestinal Diseases can occur in two ways: first, through the direct effect of the virus itself, and second, in connection with drug therapy used to treat coronavirus infection. Therefore, it is necessary to take into account that in this type of disease (which reaches 40%) there is an iatrogenic risk factor, which makes it more beneficial to seek treatment methods from natural and folk medicine.